Tool Development Defense Man Mannequin Basketball - Meysi Bilgia Irawan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
This study aims to develop the Defense Man Mannequin tool as a training tool that can provide effectiveness to coaches and athletes. This tool is used to train techniques to facilitate the performance of the trainer. This research is a research development or Research and Development (R&D). The development of the model defense tool was first validated by material experts, media experts, and field trials of 8 basketball athletes for the 1st phase of the trial, 16 athletes for the 2nd phase of the trial. The subjects of this research were the basketball athletes of Club Garuda Putih, Jambi City. Data collection techniques were used in this study by using an instrument in the form of a questionnaire. The data analysis technique of this research is a descriptive qualitative and descriptive quantitative percentage. The results showed that the Defense Man Mannequin was feasible to be used as a basketball training aid. These results are obtained from the latest validation results of a) material experts by 92% or Eligible; b) media expert at 100% or appropriate; c) Athletes in the final stage of field trials are 95.3%. Thus, the conclusion is that the mannequin defense tool has been declared suitable for use as an exercise aid.